To Identify Adenomatous Polyposis Coli Gene Mutation as a Predictive Marker of Endometrial Cancer Immunotherapy - Song, Yunfeng; Huang, Jian; Wang, Kai; Li, Yiran (Frontiers in Cell and Developmental Biology, 2022)
The adenomatous polyposis coli (APC) gene is the chromatin-remodeling-related gene and a typical tumor suppressor. Patients with a high expression of programmed death-ligand 1 (PD-L1) or a high level of tumor mutational burden (TMB) may benefit from immunotherapy in endometrial cancer (EC). This study aimed to demonstrate the role of APC in the diagnosis and immunotherapy treatment of EC. We performed an integrative analysis of a commercial panel including 520 cancer-related genes on 99 tumors from an endometrial cancer cohort in China and DNA-seq data from The Cancer Genome Atlas (TCGA) to identify new gene mutations as endometrial cancer immunotherapy markers. We found that the significant mutant genes that correlated with the PD-L1 expression and TMB were related to the chromatin state and generated a discovery set having 12 mutated genes, including the APC gene, which was identified as a new marker for immunotherapy. Further analysis revealed that tumors with the APC mutation had high TMB, increased expression of PD-L1, and increased lymphocytic infiltration. Next, we verified that APC has an inactive mutation in EC, which may affect the immune response, including PD-L1 expression, microsatellite instability, and lymphocytic infiltrate. Furthermore, patients with the APC mutation had longer overall survival. Our study demonstrates that APC could play an important role in enhancing the response to endometrial cancer treatment, particularly immunotherapy.